IMPLEMENTASI ALGORITMA BACKTRACK UNTUK PENCARIAN SOLUSI KNIGHT’S TOUR PROBLEM PADA PAPAN CATUR m x n - Wamiliana Wamiliana; Dian Kurniasari; Dolly Yudhistira (Jurnal Komputasi, 2013)
This research discusses about finding all solutions of The Knight's Tour Problem. The steps done by a knight on a chess board forms a path. If the track is able to pass through all points (boxes)  and can return to the original point (box)  is called as Hamilton Cycle, that produces Closed Knight's Tour;  if the path can pass through all the points but can not return to the original point of the track is called as Open Knight's Tour. There are various ways to solve the Knight's Tour Problem, one of which is to use the Backtrack algorithm. In this paper we will discuss of finding all solutions of Knight’s Tour Problem vary from 3x3 up to 8x8 chessboards.Keywords: knight’s tour problem, backtrack algorithm, open and closed knight’s tour